Black soldier fly frass as a sustainable organic fertilizer: enhancing productivity of leafy vegetables and soil health in Benin - Santos, Carline C. J.; Dannon, Elie A.; Bougna Tchoumi, Honorine H.; Mbokou, Serge F.; Etchiha Afoha, Sètondji A. P.; Mignouna, Djana; Falade, Titilayo D. O.; Phorbee, Olapeju; Chougourou, Daniel C.; Tematio, Paul; Ndindeng, Sali A.; Djouaka, Rousseau (Frontiers in Plant Science, 2026)
Soil nutrients depletion directly threatens sustainability of food systems by reducing agricultural productivity, degrading ecosystem services, thus increasing the need for external inputs. Frass, a nutrient-rich byproduct of insect farming, is increasingly recognized for its potential in sustainable agriculture. In the current study, we explored the effects of composted Black Soldier Fly (BSF) frass on the growth and yield of Solanum macrocarpon (African eggplant) and Lactuca sativa (Lettuce), as well as its effect on soil nutrient composition, compared to poultry manure and inorganic fertilizers (NPK and urea). Two field experiments were conducted separately for lettuce and the African eggplants, each involving six treatments and four replicates per crop species. For lettuce, treatments included: BSF frass at 20 t/ha (T1), poultry manure at 20 t/ha (T2), BSF frass at 20 t/ha + 100 kg/ha urea (T3), BSF frass at 10 t/ha + 100 kg/ha urea (T4), NPK (15:15:15) at 200 kg/ha + 100 kg/ha urea as positive control (T01), and unfertilized soil as negative control (T0). For African eggplant, treatments consisted of: BSF frass at 15 t/ha (T1), 10 t/ha (T2), and 5 t/ha (T3), poultry manure at 10 t/ha (T4), NPK (15:15:15) at 200 kg/ha + 100 kg/ha urea as positive control (T01), and unfertilized soil as negative control (T0). Plant growth parameters like plant height, number and size of leaves and yield were analyzed. The results showed that, BSF frass at 20t/ha and 10t/ha significantly performed better than the other fertilizers in promoting plant growth and increasing yield in lettuce (3.53 kg per 3m2 and 5.12 kg per 3m2 in season 1 and 2, respectively) and of the African eggplant (5.04 kg per m2). Yield improvements reached approximately 50% compared with inorganic fertilizer treatments. Post-harvest soil analysis showed significant differences among treatments for African eggplant in nitrogen (N), phosphorus (P), potassium (K), and electrical conductivity (EC), while for lettuce, only soil pH differed significantly. These findings suggest that BSF frass is a viable alternative to both inorganic and organic fertilizers, offering a sustainable solution for improving crop productivity and soil health.